1992
DOI: 10.1042/bst020155s
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin immunoreactivity of multiple polypeptides in rat brain synaptic membranes

Abstract: The low molecular weight polypeptide ubiquitin is commonly found conjugated to other protein species. The ubiquitin moiety has a well characterised role in targetting many of these proteins for rapid degradation [reviewed in I]. Some ubiquitin conjugates however, such as the ubiquitinated histones H2A and H2B, appear to be long-lived and formed reversibly [2]. There is limited evidence for the ubiquitination of cell-surface proteins, for instance, the lymphocyte homing receptor LECAM-1 [reviewed in 31. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Whether CDCrel-1 regulates dopamine release awaits further clarification, but failure of CDCrel-1 to be degraded by familial-linked Parkin mutations could increase the steady-state level of CDCrel-1 and thus potentially inhibit dopamine release and contribute to a Parkinsonian state. The mechanism underlying the degradation and turnover of synaptic vesicle-associated proteins has not been clarified, despite the identification of ubiquitin in the postsynaptic density and synaptic terminals (38)(39)(40). However, it is likely that Parkin or other nervous system-enriched E3s may play a prominent role in regulation of synaptic vesicle-associated protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Whether CDCrel-1 regulates dopamine release awaits further clarification, but failure of CDCrel-1 to be degraded by familial-linked Parkin mutations could increase the steady-state level of CDCrel-1 and thus potentially inhibit dopamine release and contribute to a Parkinsonian state. The mechanism underlying the degradation and turnover of synaptic vesicle-associated proteins has not been clarified, despite the identification of ubiquitin in the postsynaptic density and synaptic terminals (38)(39)(40). However, it is likely that Parkin or other nervous system-enriched E3s may play a prominent role in regulation of synaptic vesicle-associated protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…2 The ubiquitin-proteasome pathway plays a crucial role in the degradation of proteins involved in a variety of cellular processes, including differentiation, proliferation, and apoptosis (65,71,76). However, the role of the ubiquitin-proteasome pathway in the degradation of synaptic vesicle-associated proteins remains poorly characterized, despite the identification of ubiquitin in synaptic terminals (77,78). In this study, we have shown that synaptophysin, an integral membrane protein of synaptic vesicles, is ubiquitinated and degraded by the proteasome pathway.…”
Section: Siah Associates With the E2 Ubiquitin-conjugating Enzyme Ubcmentioning
confidence: 99%
“…The ubiquitin-proteasome pathway plays a crucial role in the degradation of proteins involved in a variety of cellular processes, including differentiation, proliferation, and apoptosis. However, the role of the ubiquitin-proteasome pathway in the degradation of presynaptic proteins remains poorly characterized, despite the presence of ubiquitin at nerve terminals (3)(4)(5). In the ubiquitin-proteasome pathway, substrates are marked for degradation by covalent linkage to ubiquitin.…”
mentioning
confidence: 99%